The use of kaolin and dolomite bed additives as an agglomeration mitigation method for wheat straw and miscanthus biomass fuels in a pilot-scale fluidized bed combustor. (August 2022) - Morris, Jonathan D.; Daood, Syed Sheraz; Nimmo, William
Abstract: Renewable biomass fuels are frequently used for power generation. Biomass ash causes bed agglomeration in fluidized bed boilers due to the formation of alkali silicate melts. Very few prior studies have tested dolomite and kaolin bed additives for agglomeration mitigation with agricultural biomasses. In this work, pelletized miscanthus and wheat straw were tested in a pilot-scale 65kWth fluidized bed combustor with varying dosages of dolomite and kaolin on a silica sand bed. Neither additive improved defluidization time with wheat straw, whereas additive use at all dosages prevented bed defluidization with miscanthus. Agglomerates were studied through a novel, detailed SEM/EDX analysis across structural features. SEM/EDX analysis presented evidence of chemical reaction between both additives and fuels. Potassium in ash migrated into kaolin particle at depths of up to 60 μm. With dolomite, calcium and magnesium raised melt temperatures. Thermochemical modelling of the ash and additive combinations predicted that additive use would substantially reduce ash melt formation. It is proposed that the wheat straw pellet acted as a "ready-made" agglomerate structure due to release of molten ash to the pellet surface which bed material then sticks to, hence the lack of change to defluidization time regardless of additive use. Future studies into this behaviour would improve additive use. Graphical abstract: Image 1